2020
DOI: 10.1016/j.envexpbot.2020.104099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drought on growth, photosynthesis and total antioxidant capacity of the saharan plant Oudeneya africana

Abstract: Highlights Oudneya africana responds to drought by increasing instantaneous and intrinsic water use efficiency, indicating that photosynthetic limitations could be due to stomatal closure. O. africana has a high capacity to restore photosynthesis after re-watering  Polyphenols, flavonoids and total antioxidant capacity increased with increasing drought stress severity thus enabling the plant to survive under adverse environmental conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 73 publications
5
31
0
1
Order By: Relevance
“…Date represent the mean ± SD (n = 7), statistically significant differences between B73 and doi57 are indicated by asterisks. * P < 0.05, df = 12 induced oxidative damage (Li et al 2019a;Talbi et al 2020). The doi57 had higher scavenging capacity for oxygen free radicals (•OH and DPPH) than did B73, especially under drought conditions (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Date represent the mean ± SD (n = 7), statistically significant differences between B73 and doi57 are indicated by asterisks. * P < 0.05, df = 12 induced oxidative damage (Li et al 2019a;Talbi et al 2020). The doi57 had higher scavenging capacity for oxygen free radicals (•OH and DPPH) than did B73, especially under drought conditions (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In the native range where soil pathogens are common, the costs of increased root flavonoid exudation are likely larger than in the introduced range where soil fungal pathogens are rare and so there may be directional selection on increased root flavonoid exudation. Third, flavonoids have many functions other than AM fungi stimulation including UV and drought tolerance [63,64], thus the introduced populations of invasive plants may produce more flavonoids to adapt to novel abiotic environments. For example, a recent study found leaf flavonoids contents in Triadica introduced ranges were closely related with UV and solar radiation [65].…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, increased release of flavonoids by roots reflects generally higher levels of flavonoids produced for other functions. Because a number of biotic and abiotic factors could affect root exudate chemicals, future work is needed to further reveal mechanisms underlying changes in root exudate chemicals in different plant populations [64].…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress enhances flavonoid accumulation [ 55 , 56 ], which, in turn, can reduce ROS accumulation, improving the antioxidant capacity and, consequently, resulting in drought acclimation [ 57 , 58 , 59 ]. Flavonoid production is one of the strategies used by native species living in extreme environments to avoid the oxidative damage caused by drought [ 118 , 119 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their antioxidant properties include reactivity to a variety of ROS [ 47 , 48 , 49 , 50 , 51 , 52 ], as well as metal chelating [ 53 , 54 ]. Drought stress enhances flavonoid accumulation [ 55 , 56 ], which, in turn, improves antioxidant capacity by reducing ROS and improving drought tolerance [ 57 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%